Mereduksi Prokrasinasi Akademik Siswa Melalui Layanan Penguasaan Konten Dengan Teknik Self-Management - Indrajati Kunwijaya; Giandra Ogy Pratama; Muh Zuhrul Anam (JURNAL KONSELING GUSJIGANG, 2018)
The purpose of this study was to reduce student academic procrastination. This research has two variables, namely the dependent variable of student academic procastination (y) and the independent variable of content mastery with the self management (x) technique. This type of research is experimental research with one-group pretest-posttest design. The sample in this research is 32 students at SMP Negeri in Purwokerto. The sample technique used is purposive sampling. Data collecting technique used is questionnaire. Data analysis technique used is descriptive analysis percentage and t-test. The result of research with t-test analysis obtained t count = 14,382 bigger than ttabel = 2,039. Ho is rejected, then there is a significant difference between the level of student academic procrastination before and after given content mastery service with self management technique.